2017
DOI: 10.1007/s10147-017-1209-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of image-guided hypofractionated proton therapy for localized prostate cancer

Abstract: Our results demonstrated the safety of HFPT for localized PCa patients in terms of acute toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 31 publications
4
31
0
Order By: Relevance
“…Details of the system have been described previously (15,16). Our methods of PT planning and delivery have been described in detail previously (17,18). Prior to PT, patients underwent gold marker implantation near or inside the tumor for target matching and replanning.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the system have been described previously (15,16). Our methods of PT planning and delivery have been described in detail previously (17,18). Prior to PT, patients underwent gold marker implantation near or inside the tumor for target matching and replanning.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome this issue for the future, hypofractionation is a promising strategy, especially for prostate cancer treatment, based on radiobiological models . In fact, several studies of hypofractionated particle beam RT for prostate cancer have been carried out, and reported the same or lower incidences of adverse events as those seen with conventional photon beam RT using standard fractionation . Further confirmation of the feasibility and efficacy of hypofractionated particle beam RT will enable an increase in patient volume and reduction in the cost per patient.…”
Section: Future Prospectsmentioning
confidence: 99%
“…13 In fact, several studies of hypofractionated particle beam RT for prostate cancer have been carried out, and reported the same or lower incidences of adverse events as those seen with conventional photon beam RT using standard fractionation. 8,21,[38][39][40]54 Further confirmation of the feasibility and efficacy of hypofractionated particle beam RT will enable an increase in patient volume and reduction in the cost per patient. Currently, the JASTRO is carrying out a multi-institutional prospective study of hypofractionated particle beam RT, using PBT for intermediate-risk and CIRT for high-risk prostate cancer.…”
Section: Future Prospectsmentioning
confidence: 99%
“…This study concluded that young men with prostate cancer continue to have excellent results with respect to 7year biochemical control and 5-year erectile function, without clinically significant urinary incontinence 5 years after proton therapy. 12 In another study (Nakajima K et al, 2018) to evaluate differences in acute toxicity among patients with localized Prostate cancer treated with either conventional fractionated proton therapy (CFPT) or HFPT, a total of 526 eligible patients were analyzed. The patients received 74 gray relative biological effectiveness equivalents [Gy (RBE)]/37 fractions for low-risk patients and 78 Gy (RBE)/39 fractions for intermediate-and high-risk patients in the CFPT group (n = 254) and 60 Gy (RBE)/20 fractions for low-risk and 63 Gy (RBE)/21 fractions for intermediateand high-risk patients in the HFPT group (n = 272).…”
Section: Physics Of Proton Beammentioning
confidence: 99%
“…This study demonstrated the safety of HFPT for localized Prostate cancer patients in terms of acute toxicity. 13…”
Section: Physics Of Proton Beammentioning
confidence: 99%